Study of Ethnic Stereotype of Young Bulgarians - Z. Ganeva (University of Sofia, 2015)
Ethnic stereotypes and prejudices as terms were examined from the point of view of the social identity theory (Tajfel, 1981). The results from a carried out longitudinal survey of stereotype and prejudices of young people of Bulgarian origin (n=1154; 453 men and 701 women; average age 21.7 years) in 6 time intervals: in 2004, 2006, 2008, 2010, 2012 and 2014, towards the in-group and the representatives of the main ethnic minorities: Turks, Roma and Jews, were presented. Through free associations, the relation between stereotypes and attitudes was studied in two social contexts: personal and community. The results show that the assessment of the minority groups is more positive in the former than in the latter context. The persons studied perceive most negatively the representatives of the Romani ethnos, more weakly negatively the Turks, and the attitudes towards the Jews are positive.